PROSES DAN MOTIF PERUBAHAN MODE BERJILBAB STANDAR KE SYARâI PADA PELAJAR MA AL IRSYAD GAJAH DEMAK - Choliq, Abdul (Islamic Communication Journal, 2018)
AbstractÂ Â Â Â Â Â Â Â Â Â Â Â Â Â Headscarves are something that is familiar to Muslim women who function as someones Muslim identity. The change in the standard veil mode to the shariah that occurs in Madrasah Aliyah students is a new thing out of the ordinary in the Madrasah. The change in the veil style is feared to trigger a negative response from the public who often perceive as a dangerous Islamic group. This study discusses the process of change using the hijab syari on students, the motive behind it and the changing attributes after using the hijab syari. The method used in this study is a qualitative method with a phenomenological approach. Data collection is done through interview and observation techniques. The results of this study indicate that the process of change towards the headscarf is done slowly by learning the source of books and the internet without studying the scholars who understand the problem of syara about hijab. Furthermore, there are two motives behind the students decision to switch to the hijab syarI, which is first: the motive for (motive because) in the form of: religious motives, psychological motives and defense motives. Second, the goal motive (in-order-to-motive) is: the motive for receiving charity and the motive for improving worship. While aspects that change after students wear the hijab syarI, namely: first, changes in physical attributes, changes in aspects of psychology and changes in idealism in worship.Â